Застосування теорії R-функцій для дослідження геометрично нелінійних коливань шаруватих пологих оболонок асиметричної будови - Курпа, Лідія Василівна; Тимченко, Галина Миколаївна; Осетров, Андрій Олександрович; Щербініна, Тетяна Євгенівна (Дніпровський національний університет імені Олеся Гончара, 2019)
Approach based on joint application of the R-functions theory and variational method is developed in order to study geometrically nonlinear vibrations of the laminated shallow shells in asymmetrical arrangement of layers. Mathematical formulation has used classical and Timoshenko’s theories. Created software is applied to investigate open shallow shells with complex plan form and different boundary conditions.
Application of the R-Functions Theory for Investigation of Geometrically Nonlinear Vibrations of Asymmetrical Laminated Shallow Shells
Keywords: теорія R-функцій; геометрично нелінійні коливання; шаруваті пологі оболонки; аналітично-числові методи